THE ROLE OF BANKING AND GOVERNMENT POLICY ON THE ECONOMIC SECTOR DURING THE COVID-19 PANDEMIC - Niu Haitao; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2021)
The Covid-19 pandemic that occurred in Indonesia greatly affected economic activity and affected the planning that had been set by the previous government. The government's main focus during the Covid-19 pandemic is on public health and safety, many policies have been made to deal with the Covid-19 pandemic that has harmed Indonesia, especially in the economic sector. Of course, with the many policies made to carry out economic recovery, it requires funds or a budget to realize these policies, for this reason, the importance of the role of banking in Indonesia's economic recovery during the Covid-19 pandemic. The results of the analysis of this article are as follows; 1) The Role of Banking in Indonesia during the covid-19 pandemic, 2) Government policies during the Covid-19 pandemic, 3) Impact of the Indonesian Economic Sector during the Covid-19 pandemic.